Effect of the crop-year on plant protection feature of sunflower - Novák, Adrienn (Acta Agraria Debreceniensis, 2013)
Our study focused on plant density reactions of sunflower hybrids on chernozem soil in years with different levels of available water (2011 and 2012). We studied factors (i.e.infections, yield) that are most affected by the amount of precipitation.However the amount of precipitation varied in 2011 (average amount of precipitation) and 2012 (drought), Sclerotinia and Diaporthe infections were significant in both years. Diaporthe was stronger in 2011 while in 2012 Sclerotinia infections were greater than average. Higher plant density provided for a favorable microclimate for pathogens meaning that increased stock density enabled enhanced infections. Maximum levels of infections in both the cases of Diaporthe and Sclerotinia were measured at a plant density level of 65 000 plants ha-1.2012 yields (control: between 2 289 and 3 261 kg ha-1, two-time treated: between 2 699 and 3 659 kg ha-1) were significantly lower compared to the results of 2011 (control: between 2 825 and 3 672 kg ha-1, two-time treated: between 3 059 and 4 059 kg ha-1). Fungicide treatments led to an increased yield in both years: 9.5% in 2011 and a notable, 15.1% growth in 2012. We applied regression analysis to calculate optimum plant density for the examined years and treatments. Based on the calculations we found that in the cases of both treatments optimum plant density was 53 000 plants ha-1, while in 2012 the optimum was higher due to lower level of infections: 56 000 plants ha-1 in the control stock and 64 000 plants ha-1 in the stock treated twice.